Energy balance of biodiesel production from canola - Silva,Luis Felipe Lima e (2017)
ABSTRACT: The aim of the present study was to estimate the energy balance (output/input ratio) of the canola crop for biodiesel production, under Brazilian conditions. Fossil energy expended in the production of 600kg of oil per hectare was 7,146,537kcal. The estimated energy yield per hectare was 9,930,000kcal from the production of 1,500kg ha-1 of seeds (40% oil and 60% oil cake), which resulted in an energy balance of 1.39. Results indicated the viability of biofuel production from canola, but also showed the need to improve the technology used to increase the energy and economic balance ratios.